Pengembangan Media Crossword Puzzle dalam Meningkatkan Hasil Belajar Siswa Mata Pelajaran IPAS Kelas III D MI NU Metro Lampung - Alvitriani, Alvitriani; Mahmudah, Masrurotul; Aisyah, Nurul (Jurnal Simki Pedagogia, 2025)
This research is a development research (R&D) that aims to develop Crossword Puzzle learning media in the subject of Science on the material about the characteristics of living things in order to improve student learning outcomes. The model used in this study is the 4D model consisting of 4 stages, namely Define, Design, Development and Disseminate. At the develop stage, the researcher validated the media expert and material expert. The subjects of this study were 24 students in class III D in a trial at MI NU Metro Lampung. The results of the study showed the results of media expert validation of 82%, material expert validation of 84% with the criteria "Very valid". The percentage of validity in the student response questionnaire was 88% in a large-scale trial with the category "Very good". Based on the development research conducted on the Crossword Puzzle media to improve student learning outcomes covering 3 domains. This study shows a significant increase in these three aspects where students are more motivated and active in learning, gain a better understanding of the learning material and are able to develop skills relevant to the topics being studied. It can be concluded that the Crossword Puzzle media can improve learning outcomes in the classroom learning process.